KARAKTER PENYIAR KREATIF DALAM SIARAN BERITA DI RADIO SEILA 104.3FM BATAM - Angga Aminudin; Nani Nurani Muksin (Program Studi Komunikasi dan Penyiaran Islam, 2022)
As a media provider of information, each radio has its own concept in carrying out its broadcast format. As in Indonesia, there are many radios with various broadcast formats with multi-segment listeners. Radio Seila FM Batam has a general broadcast format, in the sense of combining entertainment, news and music in one broadcast format with Islamic religious nuances. It turns out that in a few years, the program that is most in demand by listeners is the program